A CMOS analog driver for high-resolution display dedicated to portable applications - He, Zhenbo (Nanyang Technological University, 2021)
Low-voltage low-power design has become a hot spot for analog integrated circuit. This work is focused on the design of a low power consumption CMOS analog driver, which is a fundamental building block in high-resolution display for widely-used portable applications in advanced technology node. The driver requires compactness in architecture for saving silicon area and needs ability to drive high capacitive load whilst supporting fast settling time with low power supply. In this project, a low-voltage four-stage operational amplifier that provides a feasible solution called Nested Cross Feedforward Miller RC Compensation (NCFMRC) technique for realizing high-resolution driver functions for portable applications in TSMC 40nm CMOS technology is proposed. The performance of this amplifier compares excellently in terms of figures-of-merit (FOM) with respect to that of the previous works. Most importantly, this work is able to drive heavy capacitive load with only 6uA of the whole circuits. It has achieved gain enhancement of over 80dB and bandwidth extension of 1MHz whilst displaying good phase margin and stability among different processes and temperatures at the same time. The proposed amplifier will be useful for low-voltage high-capacitance signal processing applications in System-on-Chips (SoC) or Internet-of-Things (IoT).